Emerging Non-statin Treatment Options for Lowering Low-Density Lipoprotein Cholesterol - Bardolia, Chandni; Amin, Nishita Shah; Turgeon, Jacques (Frontiers in Cardiovascular Medicine, 2021)
Low-density lipoprotein cholesterol is a modifiable risk factor for the development of atherosclerotic cardiovascular disease. Statins have been the gold standard for managing cholesterol levels and reducing the risks associated with atherosclerotic cardiovascular disease; however, many patients do not achieve their cholesterol goals or are unable to tolerate this drug class due to adverse drug events. Recent studies of non-statin cholesterol-lowering drugs (i.e., ezetimibe, PCSK9 inhibitors) have demonstrated cardiovascular benefits; and new drugs (i.e., bempedoic acid, inclisiran) have produced promising results in pre-clinical and clinical outcome trials. This narrative review aims to discuss the place in therapy of ezetimibe, PCSK9 inhibitors, bempedoic acid, and inclisiran and describe their relative pharmacokinetic profiles, efficacy and safety as monotherapy and combination therapy, and cardiovascular benefit(s) when used for hypercholesterolemia.